Correction to: Community participation and private sector engagement are fundamental to achieving universal health coverage and health security in Africa: reflections from the second Africa health forum - Olushayo Olu; Pamela Drameh-Avognon; Emil Asamoah-Odei; Francis Kasolo; Tomas Valdez; Grace Kabaniha; Humphrey Karamagi; Suvajee Good; Helena O’Malley; Zabulon Yoti; Nirina Razakazoa; Etienne Minkoulou; et al. (BMC Proceedings, 2019)
Following publication of the original article [1], the authors reported the following author name error is the article: